PERLINDUNGAN HUKUM BAGI KONSUMEN TERHADAP PIDANA PINIPUAN JUAL BELI BARANG BERMEREK SECARA ONLINE YANG CACAT PRODUK - Riswanda Aulia R. Harahap, Bonanda Japatani Siregar (NERACA KEADILAN, 2025)
Globalization facilitates buying and selling transactions so that online transaction mechanisms are born which of course have negative and positive impacts so that product sales occur in the form of unauthorized use of brands. The purpose of this study is to determine the application of criminal law and consumer protection laws against unauthorized use of brands and legal certainty regarding consumer protection in online transactions based on Law Number 8 of 1999 concerning Consumer Protection. The method used in this study is normative juridical. The conclusions in the study include the application of material criminal law to perpetrators of online fraud in the sale and purchase of branded goods that are defective. Products can be seen from perpetrators of online fraud who offer branded goods but turn out to be defective or do not match the information promised can be subject to criminal sanctions based on material criminal law, especially Article 378 of the Criminal Code concerning fraud, as well as Article 62 and Article 8 paragraph (1) letter f Law No. 8 of 1999. Legal protection for consumers based on Law Number 8 of 1999 concerning Consumer Protection can be seen in Article 19 of the Consumer Protection Law which stipulates that business actors are responsible for providing compensation to consumers for losses due to goods and/or services received that do not comply with the agreement or do not meet the requirements as promised. The legal certainty for consumer protection in online transactions based on Law Number 8 of 1999 concerning Consumer Protection can be seen from the existence of a mechanism to provide legal certainty for consumers who feel disadvantaged through the BPSK that exists throughout Indonesia. Although in practice there are still challenges such as limited access to BPSK throughout Indonesia, as well as limited consumer legal literacy to use legal channels effectively.